Exploring Self-Awareness Skills in Junior High School English Textbooks: A Social Emotional Learning Perspective - Yulia Amanda; Ria Saraswati (Yayasan pendidikan dzurriyatul Quran, 2026)
This study examines the representation of self-awareness skills in junior high school English textbooks from the perspective of Social Emotional Learning (SEL). This topic is important because English language learning is not only directed toward the mastery of linguistic competence but also toward the development of students’ self-awareness, emotional recognition, values, identity, and personal potential. This study employed a qualitative approach using content analysis. The data source was the Grade IX English for Nusantara textbook, which was analyzed based on self-awareness indicators within the SEL framework. The data were examined through verbal and visual representations found in learning materials, dialogues, instructions, activities, and illustrations. The findings show that self-awareness skills are represented more dominantly through verbal elements than visual elements. Verbal representations appear in reading texts, dialogues, reflective questions, and learning tasks, while visual representations function mainly as supporting elements. The most prominent aspects are related to identifying personal, cultural, and linguistic assets, as well as connecting feelings, values, and thoughts. These findings indicate that English textbooks have significant potential to integrate students’ social and emotional development into language learning.